2019
DOI: 10.7755/fb.117.1-2.12
|View full text |Cite
|
Sign up to set email alerts
|

Age determination and growth of the blue shark (Prionace glauca) in the western North Pacific Ocean

Abstract: Accurate estimation of growth parameters is vital for stock assessments and management of exploited species. To determine if changes in sex-specific growth parameters of the blue shark (Prionace glauca) have occurred in the North Pacific Ocean following population declines in the 1980s and 1990s, we analyzed data obtained from the vertebrae of 659 male and 620 female sharks that had precaudal lengths (PCLs) of 33.4-258.3 cm and were captured over a wide geographic area between 2010 and 2016. Maximum counts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Based on our age data from the MP, it can be concluded that juveniles of I. oxyrinchus have a relatively fast growth rate, as has previously been reported for the species in the NPO (Kai et al ., 2015) and Northwest Atlantic (Branstetter, 1990), with implications for their biological productivity and resilience to fishing. The growth of the species is similar to that of other oceanic species, such as blue ( Prionace glauca ) and thresher sharks ( Alopias pelagicus ), with similar growth coefficients reported for both females ( k = 0.15/0.09 year −1 ) and males ( k = 0.12/0.12 year −1 ) (Fujinami et al ., 2019; Liu et al ., 1999). Our results provide an insight into the population structure, with greater precision for neonates and juvenile growth.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our age data from the MP, it can be concluded that juveniles of I. oxyrinchus have a relatively fast growth rate, as has previously been reported for the species in the NPO (Kai et al ., 2015) and Northwest Atlantic (Branstetter, 1990), with implications for their biological productivity and resilience to fishing. The growth of the species is similar to that of other oceanic species, such as blue ( Prionace glauca ) and thresher sharks ( Alopias pelagicus ), with similar growth coefficients reported for both females ( k = 0.15/0.09 year −1 ) and males ( k = 0.12/0.12 year −1 ) (Fujinami et al ., 2019; Liu et al ., 1999). Our results provide an insight into the population structure, with greater precision for neonates and juvenile growth.…”
Section: Discussionmentioning
confidence: 99%
“…There would be the differences between otolith processing methods and its interpretation. Accurate estimation of growth parameters is vital for stock assessments and management of exploited species (Fujinami et al 2019). Mendoza (2006) also noted that accurate size-at-age and age-at-first maturity estimations are highly important for conservation and management of exploitable fishery resources.…”
Section: Discussionmentioning
confidence: 99%
“…The birthmark was identified by a change in the angle of the inner margin of the corpus calcareum , exhibiting the transition from pre‐ to postnatal growth, thus, established as age zero (Goldman et al, 2012) (Figure 2). The vertebral radius (VR) was measured from the focus to the edge of the centrum of the vertebrae perpendicular to the direction of the cutting plane (Fujinami et al, 2019) using the measuring programme ImageJ (Schneider et al, 2012). The VR to FL relationship was estimated by using a linear regression and was compared by sex using the ANCOVA.…”
Section: Methodsmentioning
confidence: 99%
“…2). The vertebral radius (VR) was measured from the focus to the edge of the centrum of the vertebrae perpendicular to the direction of the cutting plane (Fujinami et al, 2019) using the measuring programme ImageJ (Schneider et al, 2012). The VR to FL relationship was estimated by using a linear regression and was compared by sex using the ANCOVA.…”
Section: Vertebral Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation